Answer:
C) (6 x 3) - 18 ÷ 9
Explanation:
I'll solve this question by writing down every step and doing it one by one.
1. Multiply 6 by 3
--> This will be represented as 6 x 3.
2. Subtract the quotient of 18 and 9
--> The quotient is a number resulting in a division of another number. In this case, 18 is bigger than 9, so the quotient will be: 18 ÷ 9.
--> Since we are subtracting this from the equation we got earlier, it can be expressed as (6 x 3) - (18 ÷ 9)
This equation is the same as C) (6 x 3) - 18 ÷ 9, so C is our final answer.